2013
DOI: 10.1056/nejmoa1202657
|View full text |Cite
|
Sign up to set email alerts
|

Topical Paromomycin with or without Gentamicin for Cutaneous Leishmaniasis

Abstract: This trial provides evidence of the efficacy of paromomycin-gentamicin and paromomycin alone for ulcerative L. major disease. (Funded by the Department of the Army; ClinicalTrials.gov number, NCT00606580.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(137 citation statements)
references
References 23 publications
5
127
0
5
Order By: Relevance
“…Topical antileishmanial treatments containing paramomycin daily for 20 days have proven effective for the treatment of CL caused by L. major. 32,33 Topical treatments that can be managed at the primary care level or even as home-based care could overcome many of the technical impediments for local treatment of CL in children. However, in addition to being an experimental formulation and hence, unavailable, the efficacy and effectiveness of paramomycin for New World CL have not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Topical antileishmanial treatments containing paramomycin daily for 20 days have proven effective for the treatment of CL caused by L. major. 32,33 Topical treatments that can be managed at the primary care level or even as home-based care could overcome many of the technical impediments for local treatment of CL in children. However, in addition to being an experimental formulation and hence, unavailable, the efficacy and effectiveness of paramomycin for New World CL have not been established.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the emergence of pronounced parasite drug resistance in some regions, relatively high costs, and/or the severe toxic effects, there has been an extensive search over the last few years for new therapeutic agents. Paromomycin, a clinically approved AG for the treatment of various bacterial and parasitic infections, is the major component of a topical ointment (Leishcutan) used to treat cutaneous leishmaniasis caused by several species of parasites, and attempts have been made to further improve existing formulations (13)(14)(15). Paromomycin is also effective against visceral leishmaniasis, the fatal form of this disease (16), and it is registered in India and Nepal.…”
mentioning
confidence: 99%
“…3 Paramomycin has recently been shown to be an effective topical treatment of CL in adults. 12 Although we could not find any published trials recommending paramomycin for L. tropica CL in children, literature reports 80% response to paramomycin for Leishmania major CL in studies which included children. 12 Neal and others found that in mouse models, aminosidine (chemically identical to paromomycin) showed high activity against amastigotes of all strains of L. major and L. tropica.…”
Section: Discussionmentioning
confidence: 72%